Analysis of Supplier Selection of Plate Raw Material (Case Study: PT XYZ) - Dewie Saktia Ardiantono; Bustanul Arifin Noer; Dhea Elvira Rosa; M. Ubaidillah Al Mustofa (Jurnal Sosial Humaniora, 2025)
PT. XYZ is one of the State-Owned Enterprises of Strategic Industries (BUMNIS) which runs the business field of Project Management and Services (MPJ) and Machinery and Equipment Industry (MPI). Currently the company is experiencing problems of not achieving the sales growth target in 2012-2016. This problem is caused mainly by one of the problems in supply chain, namely the delay of raw materials on the project undertaken. From the results of previous study, it was found that supplier selection evaluation has the highest value of the total effectiveness to difficulty ratio (ETDk); therefore, evaluation on supplier selection should be done in order to establish good integration. The method used is Analytical Hierarchy Process. Criteria that have been determined is the price, delivery, quality, and service. As a result, the sub criteria of price and quality compliance has the highest value and the first supplier is the best supplier.